2006
DOI: 10.1074/jbc.m510311200
|View full text |Cite
|
Sign up to set email alerts
|

A G316A Mutation of Manganese Lipoxygenase Augments Hydroperoxide Isomerase Activity

Abstract: Lipoxygenases with R stereospecificity have a conserved Gly residue, whereas (S)-lipoxygenases have an Ala residue. Site-directed mutagenesis has shown that these residues control position and S/R stereospecificity of oxygenation. Recombinant Mn-LO was expressed in Pichia pastoris, and its conserved Gly-316 residue was mutated to Ala, Ser, Val, and Thr. The G316A mutant was catalytically active. We compared the catalytic properties of Mn-LO and the G316A mutant with 17:3n-3, 18:2n-6, 18:3n-3, and 19:3n-3 as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 52 publications
(64 reference statements)
3
33
0
Order By: Relevance
“…Oxygen Access-As previously reported, G332A⅐13R-MnLOX augmented the hydroperoxide isomerase activity and the formation of epoxy alcohols from 13R-HPOTrE (38). We found that L336F⅐13R-MnLOX also possessed prominent hydroperoxide isomerase activity.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Oxygen Access-As previously reported, G332A⅐13R-MnLOX augmented the hydroperoxide isomerase activity and the formation of epoxy alcohols from 13R-HPOTrE (38). We found that L336F⅐13R-MnLOX also possessed prominent hydroperoxide isomerase activity.…”
Section: Discussionsupporting
confidence: 77%
“…This is also in analogy with G332A, which only slightly increased the oxygenation at C-9 (38). K m for 18:3n-3 remained in the low M range for L336F (Table 2).…”
Section: Replacement Of Leu 336 and Gly 332 With Larger Hydrophobic Rsupporting
confidence: 70%
See 3 more Smart Citations